Pembangunan Wilayah Berbasis Potensi Wisata Halal di Banten - Lusi Cahaya Purnama; Hidayanti, Dina; Safitri, Mamah Anis (CV Putra Publisher, 2024)
Banten Province, with its rapid growth and diverse tourism potential, presents significant opportunities for developing halal tourism. Halal tourism, guided by Islamic Sharia principles, has become increasingly crucial in the global context today. The aim of this research is to analyze the potential, development, opportunities, and challenges in developing halal tourism in Banten Province. The research methodology employed in this article involves a qualitative approach. Qualitative methods are utilized to explore the perspectives and perceptions of the community towards halal tourism, as well as to understand relevant cultural values. Data sources for this research include secondary data. Secondary data may originate from related literature, government reports, tourism industry publications, and other relevant sources of information. The data collection technique involves literature review. The research findings provide a profound understanding of the potential of halal tourism in Banten Province and evaluate the challenges and opportunities for sustainable industry development. Therefore, this article makes a significant contribution to supporting the vision of Banten Province as a leading destination for halal tourism at both national and global levels.